A lithium battery negative electrode film and preparation method thereof
Through solvent-free thermal method and high-temperature and high-pressure extrusion molding process, a lithium battery negative electrode film that is not easy to lose powder and has high compaction density was prepared, which solved the uneven dispersion of the electrode film, adhesive residue and long process cycle in the prior art. The problem of improving the energy density and cycle life of the battery.
Patent Information
- Application Number
- CN202210263213.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-03-17
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2042-03-17
AI Technical Summary
In the coating process of the existing lithium battery negative electrode film, there are problems such as uneven dispersion of electrode film paste, uneven distribution of conductive agent, residual adhesive, low electrode compaction density, long process cycle and uneven surface, which affects the battery. energy density and cycle life.
Using solvent-free thermal method and high-temperature and high-pressure extrusion molding process, N-(4-cyano-3-trifluoromethylphenyl)methyl is used through formulation design, including reasonable proportions of active substances, adhesives and conductive agents. Prepare adhesives for materials such as radical acrylamide, N-trimethylol methacrylamide, allyl furoate, N-vinyl carbazole, etc., perform high-temperature and high-pressure extrusion molding and rolling molding to prepare powders that are not easy to lose. , a lithium battery negative electrode film with high compaction density.
A lithium battery negative electrode film with no residue solvent and better environmental protection performance is realized, which improves the energy density and cycle life of the battery, shortens the process cycle, and enhances the flatness and consistency of the electrode sheet.
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium batteries, and in particular to a negative electrode film of a lithium battery and a preparation method thereof. Background Art
[0002] With the rapid increase in the number of information and communication related devices such as personal computers, camcorders and portable phones in recent years, the batteries used as power sources for these devices have developed rapidly. Among them, as the most common type of battery, lithium batteries have been widely used in various portable electronic devices due to their advantages such as high energy density, high voltage, long cycle life, low self-discharge rate, no memory effect, stable discharge voltage, fast charge and discharge, and environmental protection. They are also used as a power source in the growing field of electric vehicles.
[0003] As an important component of lithium batteries, the negative electrode membrane of lithium batteries is the main place for battery reactions. It is not only responsible for ion transmission, but also provides electronic conduction. Its quality directly affects the performance of lithium batteries. The negative electrode membrane of lithium batteries refers to the membrane containing active substances used in the negative electrode of lithium batteries. The membrane generally contains active substances (used to provide lithium ions and accept lithium elements), adhesives and conductive agents, which are bonded to the current collector to form a pole piece. The existing technology for forming negative electrode membranes of lithium batteries requires solvents such as NMP and pure water because it involves a coating process. There is a problem of uneven dispersion of the electrode membrane slurry, which is prone to serious agglomeration and affects the electrochemical performance of the battery. Uneven distribution of conductive agents will affect the electron flow of pole pieces, and uneven distribution of binders will affect the bonding strength of the coating.
[0004] At present, the coating process of negative electrode membranes for lithium batteries generally needs to deal with harmful substances such as waste gas (organic solvent volatilization); residual solvents in the coated electrode may reduce the working life of the battery; the dissolved adhesive coated on the surface of the active material will increase the battery resistivity, thereby reducing the energy density and power density of the lithium battery; the electrode compaction density is low, resulting in low energy density, high resistance and low cycle life; the process cycle is long; and the pole piece consistency is poor. The negative electrode membranes of lithium batteries on the market also have technical problems that the negative electrode is often not dried because the negative electrode material is mainly carbon material, and the two sides are prone to warping and unevenness after drying.
[0005] It can be seen that it is particularly important to develop a lithium battery negative electrode membrane and its preparation method that does not require waste gas treatment during the preparation process, has no residual solvents, has a higher compaction density, a short process cycle, is not easy to lose powder on the surface, and can effectively improve the energy density and cycle life of the battery. Summary of the invention
[0006] The main purpose of the present invention is to solve the above-mentioned technical problems, adopt a solvent-free thermal preparation strategy, use an extrusion molding process under high temperature and high pressure conditions, and through formula design, provide a lithium battery negative electrode film and its preparation method that does not require waste gas treatment during the preparation process, has no residual solvent, has a higher compaction density, a short process cycle, is not easy to powder fall off on the surface, and can effectively improve the energy density and cycle life of the battery.
[0007] To achieve the above purpose, the present invention provides a lithium battery negative electrode film, characterized in that it includes the following components in parts by weight: 60-98 parts of active material, 1-40 parts of binder, and 0.1-5 parts of conductive agent; the active material is a mixture formed by mixing carbon material, lithium titanate, nano chromium nitride, and porous nano tin dioxide in a mass ratio of (3-5):0.8:(0.1-0.3):0.2; the binder is N-(4-cyano-3-trifluoromethylphenyl) methacrylamide, N-trihydroxymethyl methacrylamide, allyl furoate, and N-vinyl carbazole through free radical polymerization.
[0008] Preferably, the carbon material is at least one of graphite, soft carbon and hard carbon; and the particle size of the active substance is 1500-2000 mesh.
[0009] Preferably, there is no special requirement for the source of the porous nano-tin dioxide. In one embodiment of the present invention, the porous nano-tin dioxide is prepared according to the method of Example 1 in CN102502794B.
[0010] Preferably, the preparation method of the adhesive comprises the following steps: adding N-(4-cyano-3-trifluoromethylphenyl) methacrylamide, N-trihydroxymethyl methacrylamide, allyl furoate, N-vinyl carbazole and an initiator to a high boiling point solvent, stirring and reacting at 50-65° C. in an inert gas atmosphere for 4-6 hours, then precipitating in water, washing the precipitated polymer with ethanol for 3-6 times, and finally drying in a vacuum drying oven at 85-95° C. to constant weight.
[0011] Preferably, the mass ratio of N-(4-cyano-3-trifluoromethylphenyl)methacrylamide, N-trihydroxymethylmethacrylamide, allyl furoate, N-vinyl carbazole, and initiator is (3-5):2:(0.3-0.6):(0.8-1.2):(0.06-0.09).
[0012] Preferably, the inert gas is any one of nitrogen, helium, neon and argon; the high boiling point solvent is at least one of dimethyl sulfoxide, N,N-dimethylformamide and N-methylpyrrolidone; and the initiator is azobisisobutyronitrile.
[0013] Preferably, the conductive agent is at least one of carbon nanotubes, graphene, and acetylene black; and the particle size of the conductive agent is 1500-2500 mesh.
[0014] Another object of the present invention is to provide a method for preparing the negative electrode film of a lithium battery, characterized in that it comprises the following steps:
[0015] Step S1, mixing the components uniformly according to the weight ratio to obtain a mixed material;
[0016] Step S2, extruding the mixed material through a high temperature and high pressure extrusion device, and forming it through a slit die;
[0017] Step S3, rolling and shaping and laminating with the current collector; finally rolling up to obtain a finished negative electrode film for a lithium battery.
[0018] Preferably, the high temperature and high pressure extrusion equipment in step S2 is any one of a single screw extruder, a twin screw extruder, a three screw extruder and a piston heating extruder; more preferably, the high temperature and high pressure extrusion equipment is a three screw extruder or a piston heating extruder; the temperature of the heating part of the high temperature and high pressure extrusion equipment is 170°C-250°C.
[0019] Preferably, the extrusion pressure of the extrusion in step S2 is controlled by a pressure sensor in front of the slit die, and the control range is 5.0atm-1000.0atm, more preferably 20.0atm-200.0atm.
[0020] Preferably, the current collector in step S3 is copper foil or aluminum foil; the roller used for rolling and shaping is a steel roller, and the temperature is 40°C-150°C.
[0021] Preferably, the thickness of the negative electrode film of the lithium battery is 40 μm-200 μm.
[0022] Due to the application of the above technical solution, the present invention has the following beneficial effects:
[0023] (1) The lithium battery negative electrode film disclosed in the present invention adopts a solvent-free thermal preparation strategy and is made by an extrusion molding process under high temperature and high pressure conditions. It does not need to treat harmful substances such as waste gas (organic solvent volatilization), and has better environmental protection performance. There is no residual solvent in the electrode film, which increases the working life of the battery. The electrode film made by this method has a higher compaction density, which increases the energy density and cycle life of the battery. The process cycle is significantly shortened. Due to the loose structure caused by solvent-free volatilization, the final electrode sheet has better flatness and consistency. The surface of the negative electrode film is not easy to fall off.
[0024] (2) The lithium battery negative electrode film disclosed in the present invention includes the following components by weight: 60-98 parts of active material, 1-40 parts of binder, and 0.1-5 parts of conductive agent; the active material is selected to be 60-98 parts, too little will affect the battery energy density, and too much will easily cause powder to fall off; the binder is selected to be 1-40 parts, too little will make it impossible to form a film, and too much will affect the battery energy density; the conductive agent is selected to be 0.1-5 parts, too little will result in low electronic conductivity, and too much will affect the battery energy density. Through the reasonable selection of each component and its formula, the manufactured lithium battery negative electrode film is not easy to fall off, the battery using it has a high energy density, a long cycle life, and a high electronic conductivity.
[0025] (3) The lithium battery negative electrode membrane disclosed in the present invention comprises a mixture of carbon material, lithium titanate, nano-chromium nitride and porous nano-tin dioxide in a mass ratio of (3-5):0.8:(0.1-0.3):0.2; the components cooperate with each other to make the negative electrode membrane more active, thereby effectively improving the energy density and cycle life of the battery.
[0026] (4) The negative electrode film of the lithium battery disclosed in the present invention, wherein the adhesive is made of N-(4-cyano-3-trifluoromethylphenyl) methacrylamide, N-trihydroxymethyl methacrylamide, allyl furoate, and N-vinyl carbazole through free radical polymerization. Through the interaction between the monomer structures, the bonding performance and performance stability can be enhanced, so that the shape of the electrode film itself is stable and the adhesion between the electrode film and the current collector is strong; compared with traditional polyvinylidene fluoride adhesives, it has advantages in cost and processing performance. DETAILED DESCRIPTION
[0027] The following description is used to disclose the present invention so that those skilled in the art can implement the present invention. The preferred embodiments described below are only examples, and those skilled in the art may think of other obvious variations.
[0028] The porous nano-tin dioxide involved in each embodiment of the present invention is prepared according to the method of Example 1 in CN102502794B.
[0029] Example 1
[0030] A negative electrode membrane for a lithium battery comprises the following components in parts by weight: 60 parts of an active substance, 10 parts of a binder, and 0.5 parts of a conductive agent; the active substance is a mixture of a carbon material, lithium titanate, nano-chromium nitride, and porous nano-tin dioxide in a mass ratio of 3:0.8:0.1:0.2; the binder is made of N-(4-cyano-3-trifluoromethylphenyl) methacrylamide, N-trihydroxymethyl methacrylamide, allyl furoate, and N-vinyl carbazole through free radical polymerization; the carbon material is graphite; and the particle size of the active substance is 1500 meshes.
[0031] The preparation method of the adhesive comprises the following steps: adding N-(4-cyano-3-trifluoromethylphenyl) methacrylamide, N-trihydroxymethyl methacrylamide, allyl furoate, N-vinyl carbazole and an initiator into a high boiling point solvent, stirring and reacting at 50°C for 4 hours in an inert gas atmosphere, then precipitating the polymer in water, washing the precipitated polymer with ethanol for 3 times, and finally drying the polymer in a vacuum drying oven at 85°C to a constant weight.
[0032] The mass ratio of the N-(4-cyano-3-trifluoromethylphenyl)methacrylamide, N-trihydroxymethylmethacrylamide, allyl furoate, N-vinyl carbazole and initiator is 3:2:0.3:0.8:0.06; the inert gas is nitrogen; the high boiling point solvent is dimethyl sulfoxide; and the initiator is azobisisobutyronitrile.
[0033] The conductive agent is carbon nanotubes; the particle size of the conductive agent is 1500 meshes.
[0034] A method for preparing the negative electrode film of a lithium battery comprises the following steps:
[0035] Step S1, mixing the components uniformly according to the weight ratio to obtain a mixed material;
[0036] Step S2, extruding the mixed material through a high temperature and high pressure extrusion device, and forming it through a slit die;
[0037] Step S3, rolling and shaping and laminating with the current collector; finally rolling up to obtain a finished negative electrode film for a lithium battery.
[0038] The high temperature and high pressure extrusion equipment in step S2 is a three-screw extruder; the temperature of the heating part of the high temperature and high pressure extrusion equipment is 170° C.; the extrusion pressure of the extrusion is controlled by a pressure sensor in front of the slit die and is controlled to be 20.0 atm.
[0039] The current collector in step S3 is copper foil; the roller used for rolling and shaping is a steel roller, and the temperature is 40°C.
[0040] The thickness of the negative electrode film of the lithium battery is 40 μm.
[0041] Example 2
[0042] A negative electrode membrane for a lithium battery comprises the following components in parts by weight: 75 parts of an active substance, 20 parts of a binder, and 2 parts of a conductive agent; the active substance is a mixture of a carbon material, lithium titanate, nano-chromium nitride, and porous nano-tin dioxide in a mass ratio of 3.5:0.8:0.15:0.2; the binder is prepared by free radical polymerization of N-(4-cyano-3-trifluoromethylphenyl) methacrylamide, N-trihydroxymethyl methacrylamide, allyl furoate, and N-vinyl carbazole; the carbon material is soft carbon; and the particle size of the active substance is 1600 meshes.
[0043] The preparation method of the adhesive comprises the following steps: adding N-(4-cyano-3-trifluoromethylphenyl) methacrylamide, N-trihydroxymethyl methacrylamide, allyl furoate, N-vinyl carbazole and an initiator into a high boiling point solvent, stirring and reacting at 55°C in an inert gas atmosphere for 4.5 hours, then precipitating in water, washing the precipitated polymer with ethanol for 4 times, and finally drying in a vacuum drying oven at 87°C to constant weight.
[0044] The mass ratio of the N-(4-cyano-3-trifluoromethylphenyl) methacrylamide, N-trihydroxymethyl methacrylamide, allyl furoate, N-vinyl carbazole and initiator is 3.5:2:0.4:0.9:0.07; the inert gas is helium; the high boiling point solvent is N,N-dimethylformamide; and the initiator is azobisisobutyronitrile.
[0045] The conductive agent is graphene; the particle size of the conductive agent is 1800 meshes.
[0046] A method for preparing the negative electrode film of a lithium battery comprises the following steps:
[0047] Step S1, mixing the components uniformly according to the weight ratio to obtain a mixed material;
[0048] Step S2, extruding the mixed material through a high temperature and high pressure extrusion device, and forming it through a slit die;
[0049] Step S3, rolling and shaping and laminating with the current collector; finally rolling up to obtain a finished negative electrode film for a lithium battery.
[0050] The high temperature and high pressure extrusion equipment in step S2 is a piston-type heating extruder; the temperature of the heating part of the high temperature and high pressure extrusion equipment is 190° C.; the extrusion pressure of the extrusion is controlled by a pressure sensor in front of the slit die and is controlled to be 80.0 atm.
[0051] The current collector in step S3 is aluminum foil; the roller used for rolling and shaping is a steel roller, and the temperature is 80°C.
[0052] The thickness of the negative electrode film of the lithium battery is 75 μm.
[0053] Example 3
[0054] A negative electrode membrane for a lithium battery comprises the following components in parts by weight: 82 parts of an active substance, 25 parts of a binder, and 3 parts of a conductive agent; the active substance is a mixture of a carbon material, lithium titanate, nano-chromium nitride, and porous nano-tin dioxide in a mass ratio of 4:0.8:0.2:0.2; the binder is made of N-(4-cyano-3-trifluoromethylphenyl) methacrylamide, N-trihydroxymethyl methacrylamide, allyl furoate, and N-vinyl carbazole through free radical polymerization; the carbon material is hard carbon; and the particle size of the active substance is 1850 meshes.
[0055] The preparation method of the adhesive comprises the following steps: adding N-(4-cyano-3-trifluoromethylphenyl) methacrylamide, N-trihydroxymethyl methacrylamide, allyl furoate, N-vinyl carbazole and an initiator into a high boiling point solvent, stirring and reacting for 5 hours at 59° C. in an inert gas atmosphere, then precipitating the polymer in water, washing the precipitated polymer with ethanol for 5 times, and finally drying the polymer in a vacuum drying oven at 90° C. to a constant weight.
[0056] The mass ratio of the N-(4-cyano-3-trifluoromethylphenyl)methacrylamide, N-trihydroxymethylmethacrylamide, allyl furoate, N-vinyl carbazole and initiator is 4:2:0.45:1:0.075; the inert gas is neon; the high boiling point solvent is N-methylpyrrolidone; and the initiator is azobisisobutyronitrile.
[0057] The conductive agent is acetylene black; the particle size of the conductive agent is 2000 mesh.
[0058] A method for preparing the negative electrode film of a lithium battery comprises the following steps:
[0059] Step S1, mixing the components uniformly according to the weight ratio to obtain a mixed material;
[0060] Step S2, extruding the mixed material through a high temperature and high pressure extrusion device, and forming it through a slit die;
[0061] Step S3, rolling and shaping and laminating with the current collector; finally rolling up to obtain a finished negative electrode film for a lithium battery.
[0062] The high temperature and high pressure extrusion equipment in step S2 is a three-screw extruder; the temperature of the heating part of the high temperature and high pressure extrusion equipment is 220° C.; the extrusion pressure of the extrusion is controlled by a pressure sensor in front of the slit die and is controlled to be 120.0 atm.
[0063] The current collector in step S3 is copper foil; the roller used for rolling and shaping is a steel roller, and the temperature is 110°C.
[0064] The thickness of the negative electrode film of the lithium battery is 130 μm.
[0065] Example 4
[0066] A negative electrode membrane for a lithium battery comprises the following components in parts by weight: 90 parts of an active substance, 35 parts of a binder, and 4.5 parts of a conductive agent; the active substance is a mixture of a carbon material, lithium titanate, nano-chromium nitride, and porous nano-tin dioxide in a mass ratio of 4.5:0.8:0.25:0.2; the binder is prepared by free radical polymerization of N-(4-cyano-3-trifluoromethylphenyl) methacrylamide, N-trihydroxymethyl methacrylamide, allyl furoate, and N-vinyl carbazole; the carbon material is a mixture of graphite, soft carbon, and hard carbon in a mass ratio of 1:2:2; and the particle size of the active substance is 1900 meshes.
[0067] The preparation method of the adhesive comprises the following steps: adding N-(4-cyano-3-trifluoromethylphenyl) methacrylamide, N-trihydroxymethyl methacrylamide, allyl furoate, N-vinyl carbazole and an initiator into a high boiling point solvent, stirring and reacting at 63°C in an inert gas atmosphere for 5.5 hours, then precipitating in water, washing the precipitated polymer with ethanol for 6 times, and finally drying in a vacuum drying oven at 93°C to constant weight.
[0068] The mass ratio of the N-(4-cyano-3-trifluoromethylphenyl)methacrylamide, N-trihydroxymethylmethacrylamide, allyl furoate, N-vinyl carbazole and initiator is 4.5:2:0.55:1.1:0.085; the inert gas is argon; the high boiling point solvent is dimethyl sulfoxide; and the initiator is azobisisobutyronitrile.
[0069] The conductive agent is a mixture of carbon nanotubes, graphene and acetylene black in a mass ratio of 1:3:1; the particle size of the conductive agent is 2300 meshes.
[0070] A method for preparing the negative electrode film of a lithium battery comprises the following steps:
[0071] Step S1, mixing the components uniformly according to the weight ratio to obtain a mixed material;
[0072] Step S2, extruding the mixed material through a high temperature and high pressure extrusion device, and forming it through a slit die;
[0073] Step S3, rolling and shaping and laminating with the current collector; finally rolling up to obtain a finished negative electrode film for a lithium battery.
[0074] The high temperature and high pressure extrusion equipment in step S2 is a piston-type heating extruder; the temperature of the heating part of the high temperature and high pressure extrusion equipment is 235° C.; the extrusion pressure of the extrusion is controlled by a pressure sensor in front of the slit die and is controlled to be 180.0 atm.
[0075] The current collector in step S3 is aluminum foil; the roller used for rolling and shaping is a steel roller, and the temperature is 130°C.
[0076] The thickness of the negative electrode film of the lithium battery is 180 μm.
[0077] Example 5
[0078] A lithium battery negative electrode film comprises the following components in parts by weight: 98 parts of active material, 40 parts of binder, and 5 parts of conductive agent; the active material is a mixture of carbon material, lithium titanate, nano chromium nitride, and porous nano tin dioxide in a mass ratio of 5:0.8:0.3:0.2; the binder is made of N-(4-cyano-3-trifluoromethylphenyl) methacrylamide, N-trihydroxymethyl methacrylamide, allyl furoate, and N-vinyl carbazole through free radical polymerization; the carbon material is graphite; and the particle size of the active material is 2000 meshes.
[0079] The preparation method of the adhesive comprises the following steps: adding N-(4-cyano-3-trifluoromethylphenyl) methacrylamide, N-trihydroxymethyl methacrylamide, allyl furoate, N-vinyl carbazole and an initiator into a high boiling point solvent, stirring and reacting at 65°C in an inert gas atmosphere for 6 hours, then precipitating in water, washing the precipitated polymer with ethanol for 6 times, and finally drying in a vacuum drying oven at 95°C to constant weight.
[0080] The mass ratio of the N-(4-cyano-3-trifluoromethylphenyl)methacrylamide, N-trihydroxymethylmethacrylamide, allyl furoate, N-vinyl carbazole and initiator is 5:2:0.6:1.2:0.09; the inert gas is nitrogen; the high boiling point solvent is dimethyl sulfoxide; and the initiator is azobisisobutyronitrile.
[0081] The conductive agent is acetylene black; the particle size of the conductive agent is 2500 meshes.
[0082] A method for preparing the negative electrode film of a lithium battery comprises the following steps:
[0083] Step S1, mixing the components uniformly according to the weight ratio to obtain a mixed material;
[0084] Step S2, extruding the mixed material through a high temperature and high pressure extrusion device, and forming it through a slit die;
[0085] Step S3, rolling and shaping and laminating with the current collector; finally rolling up to obtain a finished negative electrode film for a lithium battery.
[0086] The high temperature and high pressure extrusion equipment in step S2 is a three-screw extruder; the temperature of the heating part of the high temperature and high pressure extrusion equipment is 250° C.; the extrusion pressure of the extrusion is controlled by a pressure sensor in front of the slit die and is controlled to be 200.0 atm.
[0087] The current collector in step S3 is copper foil; the roller used for rolling and shaping is a steel roller, and the temperature is 150°C.
[0088] The thickness of the negative electrode film of the lithium battery is 200 μm.
[0089] Comparative Example 1
[0090] The present invention provides a negative electrode film for a lithium battery, the formula and preparation method of which are similar to those of Example 1, except that nano chromium nitride and N-vinyl carbazole are not added.
[0091] Comparative Example 2
[0092] The present invention provides a negative electrode membrane for a lithium battery, the formula and preparation method of which are similar to those of Example 1, except that porous nano-tin dioxide and allyl furoate are not added.
[0093] In order to further illustrate the beneficial technical effects of the negative electrode membranes of lithium batteries made in various embodiments of the present invention, the negative electrode membranes of lithium batteries made in various examples were cut into discs with a diameter of 14 cm and compacted, and then assembled into 2016 button batteries in a glove box filled with argon. The assembled batteries were tested for charge and discharge performance by rate charge and discharge on the LAND battery test system, and the cut-off voltage of the test was 3-4.9V. (The electrolyte was a mixture of 1.0M LiPF6 ethylene carbonate (EC) and diethyl carbonate (DEC) (volume ratio of 1:1). Nine drops of the mixture were dripped into each battery with a rubber-tipped dropper, with glass fiber filter paper as the liquid absorption membrane, PP film as the diaphragm, and the counter electrode was a disc-shaped metal lithium with a diameter of 15 mm and a thickness of 0.5 mm. The diaphragm was a Celgard2500 membrane produced by Celgard Company of the United States. It was punched into discs with a diameter of 16 mm.). The cycle stability is measured by the capacity retention rate after 100 cycles at a current density of 0.1C. The larger the value, the better the cycle stability.
[0094] The energy density test method is as follows: charge at a constant current rate of 0.5C to a voltage of 4.1V, then charge at a constant voltage of 4.1V to a current of 0.05C, at which point the lithium-ion battery reaches a fully charged state, then let stand for 5 minutes, discharge at a constant current rate of 0.5C to a voltage of 2.8V, let stand for another 5 minutes, record the capacity and voltage platform of the lithium-ion battery at a constant current rate of 0.5C, and finally measure the length, width and thickness of the lithium-ion battery. The energy density of a lithium-ion battery (Wh / L) = (capacity of a lithium-ion battery at a constant current rate of 0.5C × voltage platform of a lithium-ion battery at a constant current rate of 0.5C) / (length of a lithium-ion battery × width of a lithium-ion battery × thickness of a lithium-ion battery).
[0095] As can be seen from Table 1, the negative electrode film of the lithium battery disclosed in the embodiment of the present invention has higher energy density and better cycle stability than the comparative product, which is the result of the synergistic effect of the components. The addition of nano chromium nitride, N-vinyl carbazole, porous nano tin dioxide and allyl furoate is beneficial to improving the above properties.
[0096] Table 1
[0097] project Energy density (Wh / L) Cyclic stability (%) Example 1 545.2 92.2 Example 2 546.5 93.3 Example 3 547.5 94.0 Example 4 548.2 94.5 Example 5 549.0 95.3 Comparative Example 1 536.8 89.5 Comparative Example 2 531.7 86.9
[0098] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The above embodiments and descriptions only describe the principles of the present invention. The present invention may be subject to various changes and improvements without departing from the spirit and scope of the present invention. These changes and improvements fall within the scope of the present invention. The scope of protection claimed by the present invention is defined by the attached claims and their equivalents.
Claims
1. A negative electrode film for a lithium battery, characterized in that: The invention comprises the following components in parts by weight: 60-98 parts of active material, 1-40 parts of adhesive, and 0.1-5 parts of conductive agent; the active material is a mixture formed by mixing carbon material, lithium titanate, nano chromium nitride, and porous nano tin dioxide in a mass ratio of (3-5):0.8:(0.1-0.3):0.2; the adhesive is prepared by free radical polymerization of N-(4-cyano-3-trifluoromethylphenyl) methacrylamide, N-trihydroxymethyl methacrylamide, allyl furoate, and N-vinyl carbazole.
2. The negative electrode film of a lithium battery according to claim 1, characterized in that: The carbon material is at least one of graphite, soft carbon and hard carbon; the particle size of the active substance is 1500-2000 mesh.
3. The negative electrode film of a lithium battery according to claim 1, characterized in that: The preparation method of the adhesive comprises the following steps: adding N-(4-cyano-3-trifluoromethylphenyl) methacrylamide, N-trihydroxymethyl methacrylamide, allyl furoate, N-vinyl carbazole and an initiator into a high boiling point solvent, stirring and reacting for 4-6 hours at 50-65° C. in an inert gas atmosphere, then precipitating in water, washing the precipitated polymer with ethanol for 3-6 times, and finally drying in a vacuum drying oven at 85-95° C. to constant weight; the high boiling point solvent is at least one of dimethyl sulfoxide, N,N-dimethylformamide and N-methylpyrrolidone.
4. The negative electrode film of a lithium battery according to claim 3, characterized in that: The mass ratio of the N-(4-cyano-3-trifluoromethylphenyl)methacrylamide, N-trihydroxymethylmethacrylamide, allyl furoate, N-vinyl carbazole and initiator is (3-5):2:(0.3-0.6):(0.8-1.2):(0.06-0.09).
5. The negative electrode film of a lithium battery according to claim 3, characterized in that: The inert gas is any one of nitrogen, helium, neon and argon; the initiator is azobisisobutyronitrile.
6. The negative electrode film of a lithium battery according to claim 1, characterized in that: The conductive agent is at least one of carbon nanotubes, graphene and acetylene black; and the particle size of the conductive agent is 1500-2500 meshes.
7. The negative electrode film for a lithium battery according to any one of claims 1 to 6, characterized in that: The thickness of the negative electrode film of the lithium battery is 40 μm-200 μm.
8. A method for preparing a negative electrode film for a lithium battery according to any one of claims 1 to 6, characterized in that: The steps include: Step S1, mixing the components uniformly according to the weight ratio to obtain a mixed material; Step S2, extruding the mixed material through a high temperature and high pressure extrusion device, and forming it through a slit die; the extrusion pressure of the extrusion is controlled by a pressure sensor in front of the slit die, and the control range is 5.0atm-1000.0atm; the temperature of the heating part of the high temperature and high pressure extrusion device is 170℃-250℃; Step S3, rolling and shaping and laminating with the current collector; finally rolling up to obtain a finished negative electrode film for a lithium battery.
9. The method for preparing a negative electrode film for a lithium battery according to claim 8, characterized in that: The high temperature and high pressure extrusion equipment in step S2 is any one of a single screw extruder, a twin screw extruder, a triple screw extruder and a piston heating extruder.
10. The method for preparing a negative electrode film for a lithium battery according to claim 8, characterized in that: The current collector in step S3 is copper foil or aluminum foil; the roller used for rolling and shaping is a steel roller, and the temperature is 40°C-150°C.
Citation Information
Patent Citations
Preparation method of porous nano tin dioxide
CN102502794B
Lithium battery fabrication process using multiple atmospheric plasma nozzles
CN106797017A
Environment-friendly plastic adhesive and preparation method thereof
CN112795341A